2008
DOI: 10.1093/jnci/djm252
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Status and Efficacy of Adjuvant Anthracyclines in Early Breast Cancer: A Pooled Analysis of Randomized Trials

Abstract: The added benefits of adjuvant chemotherapy with anthracyclines appear to be confined to women who have HER2 overexpressed or amplified breast tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
159
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(168 citation statements)
references
References 20 publications
5
159
1
3
Order By: Relevance
“…Two recent pooled analyses explored the interaction between treatment and HER2 status. Gennari et al [21] analyzed 8 randomized adjuvant trials comparing anthracycline-based with non-anthracycline-based regimens in early breast cancer, which reported clinical effectiveness according to HER2 status. Anthracyclines appeared beneficial in patients with HER2-positive, but not in patients with HER2-negative tumors, with positive tests for interaction for both, disease-free and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent pooled analyses explored the interaction between treatment and HER2 status. Gennari et al [21] analyzed 8 randomized adjuvant trials comparing anthracycline-based with non-anthracycline-based regimens in early breast cancer, which reported clinical effectiveness according to HER2 status. Anthracyclines appeared beneficial in patients with HER2-positive, but not in patients with HER2-negative tumors, with positive tests for interaction for both, disease-free and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Both HER2 and TOPA2 gene status/protein expression have been reported as predictors of response in the adjuvant setting [26,27]. A pooled analysis of trials published in the literature [28] has suggested that HER2 overexpression/amplification predicts response to adjuvant anthracycline combinations. The final conclusions remains debatable as there might be a selection bias in these publications.…”
Section: Discussionmentioning
confidence: 99%
“…There appear to be a preferential antitumor activity of the anthracyclines in HER2-positive breast cancers [9,10]. Such pattern of sensitivity has been linked to the frequent association between the HER2 gene amplification and amplification of the TOPOII gene that encodes for a key intracellular target of the anthracyclines, the topoisomerase IIa enzyme [6,11]. More recent reports have challenged such mechanistic interpretation [12,13].…”
mentioning
confidence: 99%